THE INFLUENCE OF HEALTH EDUCATION ON DIETARY BEHAVIOR AND HYPERTENSION PREVENTION AMONG THE ELDERLY IN THE ULEE KARENG COMMUNITY HEALTH CENTER AREA - Alvi Salmannur; Alfia Turrahmani; Ahsanti Isra; Jihan Zhafirah Putroe Pasha; Zati Hulwani (Journal Informatic, Education and Management (JIEM), 2026)
Hypertension is one of the most common health problems experienced by older adults and is closely related to dietary patterns. A study conducted among elderly individuals in the service area of the Ulee Kareng Community Health Center, Banda Aceh, found that 69% of respondents suffered from hypertension and 63% had poor dietary habits. The analysis revealed a significant relationship between dietary patterns and the incidence of hypertension (p = 0.004). These findings highlight the important role of health education in improving public knowledge and awareness, particularly among older adults, regarding healthy eating habits. Through structured educational programs implemented within families, communities, and healthcare settings, individuals can gain a better understanding of nutritious food choices and hypertension prevention. Therefore, health education serves as an important strategy for reducing the risk of hypertension and improving the quality of life of older adults.